The Relationship of Health Behavior with Selfesteem and Selfefficacy in Students of Yazd Shahid Sadooghi University of Medical Sciences (2005) - Seid Saeed Mazloomy Mahmoodabad; Ali Mehri; Mohammad ali Morowatisharifabad (Kerman University of Medical Sciences, 2007)
Background: Health behaviors refer to activities done for maintaining supporting and improving individual health status regardless of actual or present health status There are some evidences showing direct relationship between health behavior and educational success Objective: This study was done to determine the relationship between selfesteem and selfefficacy with health behaviors among students of Yazd Shahid Sadooghi University of Medical SciencesMethods: This correlational study was performed on 309 students selected by stratified random sampling Data gathering was done by using a questionnaire that its validity and reliability had been approved respectively by experts and calculating kronbachsalpha coefficient (078 for selfesteem 87% for selfefficacy and 074 for health behavior) Results: According to the results students got 607% of the selfesteem score 623% of the selfefficacy score and 748% of the health behavior score Health behavior showed significant relationship with selfesteem (r= 014 P=0013) and selfefficacy (r= 031 P=0000) Regression analysis  showed  that  age sex family size selfesteem and selfefficacy  all together  explain 159% of  health behaviors variance and among them selfefficacy was the  most  important predicting factorConclusion: Health behavior in studied students was favorable in general but it was poor in regard to physical activity Since the results of this study showed the relationship of selfesteem and self efficacy with health behaviors and role of these factors on educational success planning for improving selfesteem self efficacy and consequently health behaviors are recommended